The Sustainable US Strategy for Leading the International System - Ewadia, Shadi Sameer (Journal of Humanities & Social Sciences, 2025)
The study aims to shed light on the US strategy to maintain its sustainable leadership of the international system and its pivotal role in shaping regional conflicts and interactions. To achieve this, the United States has formulated its strategy in a way that enhances its future leadership role, based on the conviction that the current international system is a product of purely American design, which necessitates its continued leadership and control. This strategy reflects the extent of US confidence in its ability to provide effective strategic management, especially in light of the fundamental transformations that the world witnessed after the collapse of the bipolar system, and the US took advantage of these transformations to consolidate a unipolar system under its direct leadership. The study also addresses the importance of the sustainable role of the US leadership in maintaining the stability of international peace to serve its vital interests, as it plays a key role in directing international policies in line with its strategy, strengthening its relations with its international allies and supporting the stability of the international system. Accordingly, the study emphasizes that the continuation of US leadership contributes to strengthening and sustaining its leadership position and its effective role in controlling the management of global affairs. The study relied on a descriptive and analytical approach and reached a set of conclusions, most notably that the sustainable strategy of the United States of America is based on long-term policies aimed at ensuring the continuity of its leading position in the international system, despite the potential challenges posed by future transformations in this system.